Video Pembelajaran Kasti untuk Meningkatkan Hasil Belajar Permainan Bola Kecil dan Penguatan Literasi Numerasi - Prabowo, Arif (Jurnal Didaktika Pendidikan Dasar, 2022)
Learning activities in schools must include strengthening literacy and numeracy, including Physical Education of Sports and Health (PESH) subjects. Because Indonesia is currently experiencing the Covid-19 pandemic, learning activities in schools are carried out online. One of the PESH materials is a small-ball game, namely ‘kasti’. Learning small-ball games at 1 Losari public elementary school only uses picture and theory material that is sent to students so that student learning outcomes are not optimal. In this Classroom Action Research, a learning media was made to improve learning outcomes, namely the ‘kasti’ learning video. The subjects of the research were the students of class VI 1 Losari public elementary schoolfor the academic year 2020/2021 totaling 23 students. Data collection techniques using tests and observations. As an assessment instrument, namely the observation sheet. The results of his research showed an increase in learning outcomes. This is indicated by an increase in students’ abilities in performance and the results of the basic motion of the baseball game. In addition, learning activities also strengthen students’ literacy and numeracy.